Water-based heat seal agent for flexographic printing, heat seal laminate and packaging material

JP7643225B2Active Publication Date: 2025-03-11TOYO INK MFG CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021118454
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-19
Publication Date
2025-03-11
Estimated Expiration
2041-07-19

AI Technical Summary

Benefits of technology

【0018】 本発明により、フレキソ印刷適性が良好であり、ヒートシール強度および耐ブロッキング性に優れるフレキソ印刷用水性ヒートシール剤、並びに、当該ヒートシール剤を用いたヒートシール積層体を提供することが可能となった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643225000001
    Figure 0007643225000001
  • Figure 0007643225000002
    Figure 0007643225000002
  • Figure 0007643225000003
    Figure 0007643225000003
Patent Text Reader

Abstract

To provide an aqueous heat seal agent for flexographic printing that has excellent flexographic printability, and excellent heat seal strength and blocking resistance, and a heat seal laminate including the heat seal agent.SOLUTION: An aqueous heat seal agent for flexographic printing contains an olefin-methacryl copolymer resin, and at least one selected from a polyether resin, a poly methacrylic acid resin and a poly methacrylic acid resin metal salt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous heat sealing agent for flexographic printing and a printed matter using the same. [Background technology]

[0002] In the field of packaging, packaging materials in which a heat seal agent is coated on a paper substrate or various plastic film substrates to provide a heat seal layer are widely used (Patent Document 1). A commonly known method for forming a heat seal layer is to apply a heat sealable resin composition to a substrate by printing, and then dry the medium, such as water or a solvent. Among such heat seal agents, water-based heat seal agents are desired from the standpoint of environmental friendliness, and technical development is being carried out (Patent Document 2).

[0003] For example, Patent Document 3 describes an invention on an aqueous heat-sealing agent containing an ethylene-(meth)acrylic acid copolymer resin as an ionomer. However, the aqueous heat-sealing agent is generally applied by gravure printing in many cases. On the other hand, it has been technically difficult to develop a heat-sealing agent suitable for flexographic printing.

[0004] This is thought to be because gravure printing is an intaglio printing method, which makes it easy to transfer the heat-sealing agent to the substrate, whereas flexographic printing involves a letterpress printing method for the transfer, which requires multiple transfer processes from the anilox roll to the flexographic plate and then from the flexographic plate to the substrate. As a result, the rheological properties required of the heat-sealing agent differ between gravure printing and flexographic printing, making it difficult to satisfy the suitability for flexographic printing.

[0005] Furthermore, when the resin type and / or compounding ratio is changed to make an aqueous heat sealant compatible with flexographic printing, the physical properties such as heat seal strength may not be satisfied, and it has been difficult to obtain an aqueous heat sealant that satisfies both the flexographic printing suitability and heat sealability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-165302 A [Patent Document 2] JP 2006-282968 A [Patent Document 3] Patent Publication No. 2021-31060 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an aqueous heat-sealing agent for flexographic printing which has good suitability for flexographic printing and is excellent in heat seal strength and blocking resistance, and a heat-sealable laminate using said heat-sealing agent. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using the following aqueous heat sealing agent for flexographic printing, and have thus completed the present invention.

[0009] That is, the present invention relates to an aqueous heat sealing agent for flexographic printing, which contains an olefin-(meth)acrylic copolymer resin, and at least one selected from a polyether resin, a poly(meth)acrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin.

[0010] The present invention also relates to the above water-based heat sealing agent for flexographic printing, wherein the olefin-(meth)acrylic copolymer resin contains an ethylene-(meth)acrylic acid copolymer resin.

[0011] The present invention also relates to the above water-based heat sealing agent for flexographic printing, wherein the olefin-(meth)acrylic copolymer resin has a flow midpoint temperature of 100 to 150°C.

[0012] The present invention also relates to the above aqueous heat sealing agent for flexographic printing, wherein the polyether resin is a urethane-modified polyether resin.

[0013] The present invention also relates to a heat seal laminate comprising a paper substrate and a heat seal layer made of the above-mentioned aqueous heat seal agent for flexographic printing.

[0014] The present invention also relates to the above heat sealable laminate, which further has an anchor coat layer containing a styrene-(meth)acrylic copolymer resin.

[0015] The present invention also relates to a packaging material comprising the above heat-sealable laminate.

[0016] The present invention also provides a method for producing a heat-sealable laminate having an anchor coat layer and a heat-sealable layer in this order on a paper substrate, comprising: The present invention relates to a method for producing a heat-sealed laminate, the method including the steps of: forming an anchor coat layer on the paper substrate by flexographic printing an anchor coat agent containing a styrene-(meth)acrylic copolymer resin; and then forming a heat-seal layer by flexographic printing an aqueous heat-seal agent containing an olefin-(meth)acrylic copolymer resin.

[0017] The present invention also provides a method for producing a heat-sealable laminate having an anchor coat layer and a heat-sealable layer in this order on a paper substrate, comprising: The present invention relates to a method for producing a heat-sealable laminate, the method including the steps of: forming an anchor coat layer on the paper substrate by flexographic printing an anchor coating agent; and then forming a heat-seal layer by flexographic printing the aqueous heat-sealing agent for flexographic printing. Effect of the Invention

[0018] According to the present invention, it is possible to provide an aqueous heat sealing agent for flexographic printing which has good suitability for flexographic printing and is excellent in heat seal strength and blocking resistance, and a heat seal laminate using said heat sealing agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The constituent elements of the present invention will be described in detail below, but the following is one embodiment of the present invention and the present invention is not limited thereto.

[0020] In the following description, "aqueous heat sealing agent for flexographic printing" may be written as "aqueous heat sealing agent" or "heat sealing agent", but these terms have the same meaning. In the following description, "(meth)acrylic resin" includes either or both of "methacrylic resin" and "acrylic resin". "(meth)acrylic monomer" includes either or both of "methacrylic monomer" and "acrylic monomer". For example, "(meth)acrylic acid butyl ester" includes either or both of "methacrylic acid butyl ester" and "acrylic acid butyl ester".

[0021] The aqueous heat sealing agent for flexographic printing of the present invention will be described in detail below. The present invention relates to an aqueous heat-sealing agent for flexographic printing, which contains an olefin-(meth)acrylic copolymer resin and at least one selected from a polyether resin, a poly(meth)acrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin. The olefin-(meth)acrylic copolymer resin improves heat-sealing properties, and the polyether resin, the poly(meth)acrylic acid resin, and the metal salt of a poly(meth)acrylic acid resin act to adjust the viscoelasticity of the aqueous heat-sealing agent so that it is suitable for flexographic printing. However, these requirements, including the requirements described below, act as a coherent configuration to satisfy the object of the present invention.

[0022] (Olefin-(meth)acrylic copolymer resin) In the present invention, the olefin-(meth)acrylic copolymer resin refers to a resin obtained by copolymerizing an olefin monomer and a (meth)acrylic monomer. Examples of the olefin monomer include α-olefins such as ethylene, propylene, butene, pentene, hexene, and octene, and modified products thereof. Among them, it is preferable to include ethylene. Examples of the (meth)acrylic monomer include (meth)acrylic acid, (meth)acrylic acid esters, and hydroxy(meth)acrylic acid esters. The olefin-(meth)acrylic copolymer resin exhibits a form (thermoplasticity) that is a resin that softens and has plasticity when heated at an appropriate temperature and solidifies when cooled, and imparts heat sealability to the heat seal agent. As the olefin-(meth)acrylic copolymer resin, ethylene-(meth)acrylic acid copolymer resin, etc. are preferable, and among them, ethylene-methacrylic acid copolymer resin is more preferable. The olefin-(meth)acrylic copolymer resin preferably forms an emulsion or other dispersion in water. The pH of the olefin-(meth)acrylic copolymer resin dispersion is preferably 4.0 or more and 7.5 or less. It is more preferably 4.5 or more and 7.0 or less. This is because within this range, dispersion and aggregation of the resin emulsions is suppressed, and in flexographic printing, the dispersion stability and transferability during printing are improved, and the storage stability during storage of the heat sealant is improved. The pH of the olefin-(meth)acrylic copolymer resin dispersion can be adjusted by the acid value of the resin itself, the addition of an anionic or cationic surfactant, hydrolysis, etc., and the adjustment method is not limited. The olefin-(meth)acrylic copolymer resin is preferably contained in an amount of 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, based on the total solid content of the aqueous heat sealant for flexographic printing. The amount of the olefin-(meth)acrylic copolymer resin is preferably 99.99% by mass or less, and even more preferably 99% by mass or less.

[0023] (flow midpoint temperature) The flow midpoint temperature of the olefin-(meth)acrylic copolymer resin refers to a value measured by a flow tester 1 / 2 method, and is preferably 100 to 150°C from the viewpoints of improving productivity during heat sealing processing, and improving heat seal strength and blocking resistance.

[0024] The flow midpoint temperature measured by the flow tester 1 / 2 method may be measured by a known method. Specifically, the resin sample weighed in an elevated flow tester is placed in a cylinder, and heated at a constant temperature while applying a load to the plunger inserted in the cylinder, and the temperature and plunger descent are measured. In a curve (flow tester flow curve) obtained by plotting temperature on the horizontal axis and plunger descent on the vertical axis, the temperature at the time of flowing out from the nozzle at the tip of the cylinder is defined as the flow start temperature, and the height between this flow start temperature and the highest point of the obtained S-shaped curve is defined as h, and the temperature at 1 / 2h is defined as the flow midpoint temperature measured by the flow tester 1 / 2 method.

[0025] (Ethylene-(meth)acrylic acid copolymer resin) The ethylene-(meth)acrylic acid copolymer resin may be a known one. The ethylene-(meth)acrylic acid copolymer resin is a copolymer resin containing a structural unit derived from ethylene and a structural unit derived from (meth)acrylic acid, and may be a copolymer resin in which the (meth)acrylic acid portion is partially esterified as necessary. In this case, the carboxyl group of the copolymer resin may be esterified after copolymerization, or a (meth)acrylic acid ester monomer may be used in combination during copolymerization.

[0026] The weight average molecular weight of the ethylene-(meth)acrylic acid copolymer resin is not particularly limited, but from the viewpoint of achieving both blocking resistance and heat sealing suitability, it is preferably 10,000 to 900,000, and more preferably 50,000 to 500,000.

[0027] As the acrylic acid monomer of the ethylene-(meth)acrylic acid copolymer resin, in addition to a monomer containing a carboxyl group such as acrylic acid (including methacrylic acid), various acrylic acid monomers containing functional groups such as a sulfonic acid group, a hydroxyl group, an epoxy group, a methylol group, an amino group, an amide group, etc. Also, (meth)acrylic monomers used in the styrene-(meth)acrylic acid copolymer resin described later can be used in combination as appropriate.

[0028] The ethylene-(meth)acrylic acid copolymer resin can be produced by a known method. For example, acrylic acid, an emulsifier, and a polymerization catalyst are added to water, and then a predetermined amount of ethylene gas is added to the system, heated, and emulsion polymerization is carried out to obtain an emulsion state. The conditions of temperature, pressure, and the like, and the polymerization catalyst, etc., can be those usually used and polymerization catalysts can be used. Furthermore, examples of the emulsifier include nonionic, anionic, and cationic surfactants, which can be used alone or in combination of two or more. In addition to the above surfactants, reactive surfactants having a reactive double bond, and water-soluble polymers such as polyvinyl alcohol and starch can also be used in combination.

[0029] The ethylene-(meth)acrylic acid copolymer resin may be a commercially available product, such as Chemipearl S100, S111, S120, S650, S200, S300, S420, or S500 manufactured by Mitsui Chemicals, Inc., Aquatex AC3100 or AC-M1970 manufactured by Japan Coating Resins, or Zaixen AC, A, AC-HW-10, L, NC, or N manufactured by Sumitomo Seika Chemicals.

[0030] The ethylene-(meth)acrylic acid copolymer resin is preferably used as a dispersion having a solid content of 20 to 80% by mass in terms of heat sealing suitability, flexographic printing suitability, blocking resistance, and the like.

[0031] (Polyether resin, poly(meth)acrylic acid resin, poly(meth)acrylic acid resin metal salt) In the present invention, the polyether resin, the poly(meth)acrylic acid resin, and the metal salt of poly(meth)acrylic acid resin include those that function as viscoelasticity modifiers. Viscoelasticity modifiers impart viscosity in dynamic viscoelasticity and can improve transferability to anilox-plate and plate-raw material (printed substrate) in flexographic printing. The polyether resin, the poly(meth)acrylic acid resin, and the metal salt of poly(meth)acrylic acid resin preferably form an emulsion or other dispersion in water. The pH of the polyether resin, poly(meth)acrylic acid resin, and poly(meth)acrylic acid resin metal salt dispersion is preferably 4.0 or more and 7.5 or less. The pH is preferably 4.5 or more and 7.0 or less. This is to improve the viscosity and dispersion stability of the olefin copolymer resin dispersion in flexographic printing, and to produce an effect of improving transferability. The pH of the polyether resin and / or acrylic resin dispersion can be adjusted, for example, by adding an anionic or cationic surfactant, hydrolysis, or the like, and the adjustment method is not limited. The polyether resin, poly(meth)acrylic acid resin, and poly(meth)acrylic acid resin metal salt are preferably contained in an amount of 0.01 to 40 mass %, more preferably 0.03 to 20 mass %, and even more preferably 0.05 to 10.0 mass % in the total mass of the solid content of the aqueous heat sealing agent for flexographic printing.

[0032] (Polyether resin) The polyether resin may be any resin having a polyether structure such as polyethylene oxide, polypropylene oxide, or the like, but does not include olefin-(meth)acrylic copolymer resins or styrene-(meth)acrylic copolymer resins. Examples of the polyether resin include urethane-modified polyether resins, polyethylene glycol resins, polypropylene glycol resins, polytetramethylene glycol, and polyether polyol resins such as copolymer resins thereof. Examples of the urethane-modified polyether resin include SN-Thickener 603, SN-Thickener 607, SN-Thickener 612, SN-Thickener 612N, SN-Thickener 619, SN-Thickener 621N, SN-Thickener 621TF, SN-Thickener 623N, SN-Thickener 624N, SN-Thickener 625N, SN-Thickener 629N, Nopal 700N, SN-Thickener 660T, SN-Thickener 665T, SN-Thickener A-812, and SN-Thickener A-814 manufactured by San Nopco Ltd.; and Rheolate 244, Rheolate 278, Rheolate 300, and Rheolate 212 manufactured by Elementis Japan Ltd. Examples of polyether polyol resins include SN Thickener 601, Nopal 710N, SN Thickener A-801, and SN Thickener A-816, all of which are manufactured by San Nopco. In the above, from the viewpoints of heat sealing suitability, flexographic printing suitability, and blocking suitability, it is preferable that the polyether resin contains a urethane-modified polyether resin. The weight-average molecular weight of the polyether resin is preferably 1000 to 100,000, and more preferably 5000 to 50,000. The polyether resin, together with the olefin copolymer resin, can adjust the rheology of the aqueous heat sealing agent for flexographic printing, as described in detail below.

[0033] (Urethane modified polyether resin) The urethane-modified polyether resin is obtained by modifying the above-mentioned polyether polyol resin with an isocyanate compound. As the isocyanate compound, a monoisocyanate, a diisocyanate, or the like is preferably used, and the monoisocyanate and the diisocyanate may be a known isocyanate compound used in the synthesis of a urethane resin. Examples of monoisocyanates include 2-isocyanatopropane, 2-isocyanato-2-methylpropane, isocyanatocyclohexane, 1-isocyanato-4-isopropenyl-1-methyl-cyclohexane, 4-(1-isocyanato-1-methylethyl)-1-methyl-1-cyclohexene, 1,3-dimethyl-5-isocyanatoadamantane, and 1-(1-isocyanato-1-methylethyl)-3-isopropenylbenzene (TMI). Examples of diisocyanates include 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetra ... Examples of suitable diisocyanates include phenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, and m-tetramethylxylylene diisocyanate.

[0034] (Poly(meth)acrylic acid resin and metal salt of poly(meth)acrylic acid resin) Poly(meth)acrylic acid resins and metal salts of poly(meth)acrylic acid resins are excluded from the case of olefin-(meth)acrylic copolymer resins. The poly(meth)acrylic acid resin is preferably a poly(meth)acrylic acid resin which is a polymer of a monomer containing (meth)acrylic acid, or a urethane-modified poly(meth)acrylic acid resin, which may be neutralized with a basic compound (excluding basic metal compounds). The poly(meth)acrylic acid resin metal salt is in the form of a metal salt in which the acrylic acid unit of the poly(meth)acrylic acid resin is neutralized with a basic metal compound, and is also preferably urethane-modified. Poly(meth)acrylic acid resins and metal salts of poly(meth)acrylic acid resins have a high viscoelasticity adjusting effect and promote improvement of flexographic printing suitability. As the basic compound (excluding basic metal compounds), for example, amine compounds are preferably used. Specifically, the amine compounds include ammonia, alkylamines such as diethylamine, triethylamine, and ethylenediamine, and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine. In addition, as the basic metal compounds, sodium hydroxide, potassium hydroxide, etc. are preferably used. In addition, poly(meth)acrylic acid resins and metal salts of poly(meth)acrylic acid resins can be preferably used even if they are in the form of emulsion or alkali-soluble type.

[0035] (Anchor coating agent for forming an anchor coating layer) The anchor coating agent used in the present invention is not limited, but preferably contains a styrene-(meth)acrylic copolymer resin. The components of the anchor coating agent form an anchor coating layer on the substrate and suppress the penetration of the heat sealing agent into the substrate, thereby forming a heat sealing layer with a uniform thickness on the substrate surface, and by using it together with the above heat sealing agent, the heat sealing strength and blocking resistance can be improved.

[0036] (Styrene-(meth)acrylic copolymer resin) The styrene-(meth)acrylic copolymer resin is not limited as long as it has a structural unit derived from a styrene monomer and a (meth)acrylic monomer, except for the case of an olefin-(meth)acrylic copolymer resin, a polyether resin, a poly(meth)acrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin. The (meth)acrylic monomer is preferably the following (meth)acrylic monomer. Examples of the (meth)acrylic monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, methylcyclohexyl (meth)acrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, and octadecyl (meth)acrylate. Among these, the alkyl group preferably has 1 to 6 carbon atoms, and methyl (meth)acrylate is more preferred in that it is easy to obtain good adhesion to the substrate.

[0037] The (meth)acrylic monomer may contain a hydroxyl group-containing alkyl (meth)acrylate, and examples thereof include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified (meth)acrylate; and hydroxyethyl (meth)acrylamide.

[0038] The (meth)acrylic monomer may further contain a carboxyl group-containing acrylic monomer, an amide bond group-containing (meth)acrylic monomer, an amino group-containing (meth)acrylic monomer, an aromatic ring-containing (meth)acrylic monomer, an epoxy group-containing (meth)acrylic monomer, or the like.

[0039] As the styrene-based monomer, for example, α-methylstyrene, styrene, etc. are preferably used. As the acidic monomer, for example, maleic acid, maleic anhydride, monoethyl maleic acid, itaconic acid, citraconic acid, fumaric acid, and 2-acryloyloxyethyl acid phosphate, etc. are exemplified.

[0040] In the present invention, the styrene-(meth)acrylic copolymer resin preferably contains an acidic monomer (other than the (meth)acrylic monomer) as a constituent unit in addition to styrene and the (meth)acrylic monomer.

[0041] Among the above, preferred (meth)acrylic monomers include methyl acrylate, ethyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate, and preferred acidic monomers include maleic acid and itaconic acid.

[0042] The glass transition temperature (Tg) of the styrene-(meth)acrylic copolymer resin is preferably -30 to 50°C, and is preferably -10 to 10°C from the viewpoints of improving productivity during heat sealing processing, blocking resistance, and heat seal strength. The glass transition temperature (Tg) was determined by DSC (differential scanning calorimetry). The measurement device used was a Rigaku Corporation DSC8231, with a measurement temperature range of -70 to 250°C, a heating rate of 10°C / min, and the midpoint between the endothermic start temperature and end temperature based on the glass transition in the DSC curve was taken as the glass transition temperature.

[0043] The styrene-(meth)acrylic copolymer resin may be a commercially available product, such as Joncryl PDX-7351, 7182, 7362, 7616A, 7732, 7741, 7787, 7356, 7734, 7777, 7615, 7775, 7692, 7164, 7430, 7198 manufactured by BASF, and Hi-Loss XP-8812, Hi-Loss XP-8829, Hi-Loss QE-2101, Hi-Loss QE-2149, Hi-Loss QE-2263, Hi-Loss-RE2095, Hi-Loss HE-2342, Hi-Loss NE2009, Hi-Loss KE-2536, Hi-Loss KE1095, Hi-Loss ME2243 manufactured by Seiko PMC.

[0044] (aqueous medium) In the present invention, the aqueous heat sealant for flexographic printing contains an aqueous medium. The aqueous medium contains water as a main component (50% by mass or more in the total medium) and may contain an aqueous organic solvent other than water as necessary. Specifically, it may contain an alcohol-based organic solvent or a glycol-based organic solvent depending on the printing conditions (speed, plate depth, design, drying temperature). Specific examples of the alcohol-based organic solvent include methanol, ethanol, propanol, isopropanol, isobutanol, normal butanol, tertiary butanol, hexanol, octanol, and decanol. Examples of glycol-based organic solvents include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. Among these, isopropanol, ethylene glycol, propylene glycol, etc. are preferred. From the viewpoints of storage stability, thickening, and drying properties of the aqueous heat sealant for flexographic printing, the aqueous solvent other than water is preferably 30 mass % or less, and more preferably 10 mass % or less, of the total mass of the aqueous heat sealant for flexographic printing.

[0045] (Additives) Various additives can be used in the aqueous heat sealing agent for flexographic printing and the anchor coating agent of the present invention, if necessary. For example, extender pigments, inorganic fine particles and adhesive resins, leveling agents, defoamers, waxes, and film-forming agents can be mentioned. Specifically, various additives can be mentioned, such as wax resin fine particle dispersions such as polyethylene wax for improving abrasion resistance, extender pigments such as calcium carbonate, kaolin, barium sulfate, aluminum hydroxide, clay, and talc for improving drying properties and coating film hiding properties, inorganic fine particles for imparting anti-slip properties, leveling agents for improving leveling properties, defoamers for imparting defoaming properties, basic compounds such as sodium hydroxide and potassium hydroxide for imparting resolubility, and film-forming assistants.

[0046] (Rheology adjustment of water-based heat sealant for flexographic printing) The rheology adjustment for improving transferability in flexographic printing suitability will be described. When the aqueous heat sealing agent for flexographic printing of the present invention is subjected to dynamic viscoelasticity measurement at 25° C., the loss factor tan δ at an angular frequency of 1 to 100 rad / s is preferably 1 to 100. The loss factor tan δ can be used as an index of transferability in flexographic printing, and it is sufficient if it is within the range at the angular frequency. In order to make tan δ 1 to 100, the solid mass ratio of the polyether-based resin and / or the acrylic resin in the total solid mass of the olefin-based copolymer resin and the polyether-based resin and / or the acrylic resin is preferably 0.01 to 40 mass%, more preferably 0.03 to 20 mass%, and even more preferably 0.05 to 10.0 mass%. In addition, the above range can be achieved by selecting an ethylene-methacrylic acid copolymer resin as the olefin-(meth)acrylic copolymer resin, and selecting at least one selected from a urethane-modified polyether resin, a polyacrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin. The solid content is preferably adjusted to 10 to 70% by mass, and more preferably 30 to 60% by mass. Furthermore, the viscosity at 25°C (Zahn cup viscosity No. 4) is preferably adjusted to 6 to 25 seconds, and more preferably 10 to 20 seconds. The above dynamic viscoelasticity parameters can be measured using a dynamic viscoelasticity measuring device, such as the DHR2 manufactured by TA Instruments.

[0047] (Manufacture of water-based heat sealant for flexographic printing) The aqueous heat sealant for flexographic printing of the present invention can be produced by a known method. Specifically, for example, water and an olefin copolymer resin are measured and mixed by stirring using a bladed stirrer, and then one or more of a polyether resin, a poly(meth)acrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin, and additives, etc. are added as necessary, and then further stirred and mixed uniformly to obtain the composition. The bladed stirrer can be a conventionally known one, and examples of such a stirrer include a batch type mixer such as a vessel equipped with a propeller blade, and a continuous type mixer such as an in-line mixer.

[0048] (Flexographic printing) Flexographic printing methods include the two-roll method, doctor method, and doctor chamber method. In the doctor method and doctor chamber method, an aqueous heat sealant is supplied to an anilox roll with cells formed on its surface, and excess aqueous heat sealant is scraped off from the anilox roll surface with a doctor blade. The aqueous heat sealant is then passed through a resin plate and finally printed onto the substrate. When an aqueous heat sealant is printed using the flexographic printing method, a printed product with excellent aesthetics can be obtained even on paper substrates with a rough surface.

[0049] (Flexographic printing method; Anilox roll) The anilox used in the flexographic printing used in the method for producing a flexographic printed matter of the present invention can be a ceramic anilox roll with cell engraving, a chrome-plated anilox roll, etc. The shape of the cells can be a honeycomb pattern, a diamond pattern, a helical pattern, etc., and any pattern can be used.

[0050] (Flexographic printing method; Flexographic plate) The plate used in the method for producing the printed matter of the present invention includes a photosensitive resin plate that utilizes ultraviolet curing by a UV light source, or an elastomer material plate that uses a direct laser engraving method. Any sleeve or cushion tape can be used for attaching the plate.

[0051] (Flexographic printing method; Printing machine) Flexographic printing machines include CI type multi-color flexographic printing machines and unit type multi-color flexographic printing machines, and ink supply methods include chamber methods and two-roll methods, and an appropriate printing machine can be used.

[0052] (Heat-sealed laminate) The heat-sealed laminate of the present invention can be obtained by flexographically printing the heat-sealing agent on a substrate to form a heat-sealing layer. The heat-sealed laminate preferably includes an anchor coat layer between the substrate and the heat-sealing layer. The anchor coat layer can be obtained by flexographically printing the anchor coat agent.

[0053] (Method of manufacturing a heat-sealed laminate formed from a water-based heat-sealing agent and an anchor coating agent) An example of a method for producing a heat seal laminate formed from an aqueous heat seal agent and an anchor coating agent includes a step of forming an anchor coat layer on a substrate by flexographic printing an anchor coating agent containing a styrene-acrylic resin, and then forming a heat seal layer on the anchor coat layer by flexographic printing an aqueous heat seal agent containing an olefin-(meth)acrylic copolymer resin. In the flexographic printing, a printing speed of 10 to 400 m / min is preferable. The dry coating amount of the heat seal layer and the anchor coat layer is 1 to 10 g / m. 2 It is preferable that:

[0054] Furthermore, as the printing configuration of the laminate having a heat seal layer, in addition to the configuration of the laminate described above, an overcoat layer (OP layer) and a printing layer (ink layer) can be arbitrarily combined. For the ink layer, for example, each layer and printing configuration described in JP-A-2000-025164, JP-A-2017-202142, JP-A-2020-002253, and JP-A-09-066578 can be appropriately used. The configuration of the laminate can be, for example, Substrate / Heat seal layer Base material / anchor layer / heat seal layer Ink layer / substrate / heat seal layer Ink layer / substrate / anchor layer / heat seal layer OP layer / ink layer / substrate / heat seal layer OP layer / ink layer / substrate / anchor layer / heat seal layer OP layer / base material / heat seal layer OP layer / base material / anchor layer / heat seal layer OP layer / substrate / ink layer / heat seal layer OP layer / substrate / ink layer / anchor layer / heat seal layer OP layer / Anchor layer / Base material / Anchor layer / Heat seal layer OP layer / anchor layer / base material / heat seal layer The following can be mentioned as suitable examples.

[0055] (base material) Examples of the substrate for printing (printed material) include plastic films such as polyolefin substrates such as polyethylene and polypropylene, polyester substrates such as polyethylene terephthalate, and polyamide substrates such as nylon, paper substrates, aluminum foil, and films and sheets made of composite materials thereof. In the present invention, it is particularly preferable to use a paper substrate. The paper substrate is preferably a paper substrate selected from uncoated paper, one-side glossy kraft paper in which one side of the substrate is treated, bleached kraft paper, unbleached kraft paper, and the like. EXAMPLES

[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In these examples, unless otherwise specified, "%" means "% by mass" and "parts" means "parts by mass." Furthermore, the figures for the amounts of each material in the tables are also "parts by mass."

[0057] (Solids) Approximately 1 g of the sample was weighed out and dried in a hot air circulating dryer at 150° C. for 15 minutes, after which the weight was measured. The solid content was calculated based on the following formula. Solid content = (weight of sample after drying / weight of sample before drying) x 100

[0058] (Glass transition temperature (Tg)) The glass transition temperature was determined according to the method described in JIS K 0129. Specifically, the measurement was performed by DSC (differential scanning calorimetry) using a measuring device, Rigaku Corporation's DSC8231, with a measurement temperature range of -70 to 100°C, a heating rate of 10°C / min, and the midpoint between the endothermic start temperature and end temperature based on the glass transition in the DSC curve was taken as the glass transition temperature.

[0059] (flow midpoint temperature) The water-based heat sealing agent was left at room temperature for 24 hours, and then vacuum dried at room temperature for 6 hours. Approximately 1 g of the sample was weighed out and used to measure the flow midpoint temperature by the flow tester 1 / 2 method using an elevated flow tester (Shimadzu Corporation: CFT-500). The area of ​​the tip surface of the plunger in the cylinder was 1 cm2. 2 The nozzle (discharge hole) at the tip of the cylinder had a diameter of 1 mm and a length of 1 mm. The load was 10 kgf, the starting temperature for heating was 30°C, and the heating rate was 5.0°C / min.

[0060] (Production Example 1) [Preparation of anchor coating agent S1] Anchor coating agent S1 was obtained by mixing and stirring 95 parts of styrene-acrylic copolymer resin-1 (solid content 50% by mass, glass transition temperature (Tg) 0° C.), 4.8 parts of water, and 0.2 parts of an antifoaming agent (Tegoformex 810 manufactured by Evonik, solid content 100% by mass).

[0061] (Production Examples 2 to 6) [Preparation of anchor coating agents S2 to S6] An anchor coating agent was obtained in the same manner as in Production Example 1, except that the raw materials and compositions were changed as shown in Table 1. In the table, values ​​without units indicate parts, and blanks indicate that no compound was added. The abbreviations in the table stand for the following. Styrene-acrylic copolymer resin-2 (solid content 50% by mass, glass transition temperature (Tg) 10°C) Styrene-acrylic copolymer resin-3 (solid content 50% by mass, glass transition temperature (Tg) -10°C) Styrene-acrylic copolymer resin-4 (solid content 50% by mass, glass transition temperature (Tg) -30°C) Styrene-acrylic copolymer resin-5 (solid content 50% by mass, glass transition temperature (Tg) 50°C) Acrylic resin (emulsion): Vinyblan SS-1008 (solid content 30%, glass transition temperature (Tg) 0°C)

[0062] (Example 1) [Preparation of water-based heat sealant SS1] An aqueous heat sealing agent SS1 was obtained by mixing and stirring 92 parts of an olefin-(meth)acrylic copolymer resin (ethylene-methacrylic acid copolymer resin-1; solid content 50% by mass, flow midpoint temperature 150°C), 2 parts of a urethane-modified polyether resin (SN Thickener 624N, manufactured by San Nopco, solid content 30% by mass), 5.8 parts of water, and 0.2 parts of an antifoaming agent (Tegoformex 810, manufactured by Evonik, solid content 100% by mass).

[0063] (Examples 2 to 8) [Preparation of water-based heat sealants SS2 to SS8] A water-based heat sealing agent was obtained in the same manner as in Example 1, except that the raw materials and compositions were changed as shown in Table 2. In the table, values ​​without units indicate parts, and blanks indicate that no ingredients were added. The abbreviations in the table are as follows. Ethylene-methacrylic acid copolymer resin-2; solid content 50% by mass, flow midpoint temperature 100°C Polyether resin: San Nopco Nopal 710N, solid content 30% Polyacrylic acid: Nippon Shokubai Aquaric L HL415, solids content 30% Urethane modified polyacrylic acid resin sodium salt: San Nopco SN Thickener 618 solid content 30%

[0064] (Examples 9 to 22) [Preparation of laminates L1 to L13] The anchor coating agents S1 to S6 obtained in the above manufacturing examples were used to bleach kraft pulp to produce bleached paper with a glossy surface on one side (Nagoya Bara Ryuo N, manufactured by Daio Paper Co., Ltd., with a basis weight of 60 g / m 2 ) was flexographically printed on the non-glossy side at a printing speed of 120 m / min to form a heat-seal coating film. Then, the above-mentioned water-based heat-sealing agents SS1 to SS8 were flexographically printed on the side of the above-mentioned base material coated with the anchor coating agent at a printing speed of 120 m / min to obtain a heat-sealed laminate.

[0065] (Example 23) [Preparation of laminate L14] The heat sealant SS1 obtained in the above example was used to produce bleached kraft pulp, and the resulting bleached paper (Nagoya Bara Ryuo N, manufactured by Daio Paper Co., Ltd., with a glossy surface on one side, weighing 60 g / m) was used.2 The non-glossy side of the laminate was printed twice with flexographic printing at a printing speed of 120 m / min to form a heat seal coating film, thereby obtaining a heat seal laminate L14. The transferability of the heat seal agent was evaluated as 5, the heat seal strength was evaluated as 5, and the blocking resistance was evaluated as 3.

[0066] (Comparative Examples 1 to 3) [Water-based heat sealants TT1 to TT3] A water-based heat-sealing agent was obtained in the same manner as in Example 1, except that the raw materials and compositions were changed as shown in Table 4. The abbreviations in the table stand for the following. Acrylic emulsion resin: Seiko PMC Hi-Loss PE2273 Polyethylene resin: Chemipearl A400 manufactured by Mitsui Chemicals

[0067] (Comparative Examples 4 to 6) [Preparation of Laminates M1 to M3] The anchor coating agent S1 obtained in the above manufacturing example was used to bleach kraft pulp, and the resulting bleached paper (Nagoya Bara Ryuo N, basis weight 60 g / m, manufactured by Daio Paper Co., Ltd.) with a glossy surface on one side was used. 2 ) was flexographically printed on the non-glossy side at a printing speed of 120 m / min to form a heat-seal coating film. Then, the above-mentioned water-based heat-sealing agents TT1 to TT3 were flexographically printed on the side of the above-mentioned base material coated with the anchor coating agent at a printing speed of 120 m / min to obtain a heat-sealed laminate.

[0068] (Print and evaluate) The anchor coating agents and aqueous heat sealing agents, as well as the heat sealable laminate prints obtained in the above Production Examples, Examples, and Comparative Examples, were used to carry out the following evaluations. The evaluation results are shown in Tables 3 and 5.

[0069] (Metastatic) The anchor coating agent obtained in the above manufacturing example was applied to a bleached paper (Nagoya Bara Ryuo N, basis weight 60 g / m, manufactured by Daio Paper Co., Ltd.) made of bleached kraft pulp and having a glossy surface on one side. 2) was flexographically printed on the non-glossy surface of the substrate at a printing speed of 120 m / min, and the area ratio of the anchor coating agent transferred to the substrate and the weight ratio of the anchor coating agent transferred (actual transferred weight g / m 2 Anilox roll coating amount g / m 2 The aqueous heat-sealing agent obtained in the above Examples and Comparative Examples was flexographically printed on the surface of the substrate coated with the anchor coating agent at a printing speed of 120 m / min, and the area ratio of the heat-sealing agent transferred to the surface of the substrate coated with the anchor coating agent and the transferred weight ratio of the heat-sealing agent (actual transferred weight g / m2) were calculated. 2 Anilox roll coating amount g / m 2 The value was divided by 100 and evaluated according to the following criteria. 5: The area ratio of the transferred material to the substrate is 100%, and the weight ratio of the transferred material is 30% or more. 4: The area ratio of the transferred material to the substrate is 100%, and the weight ratio of the transferred material is 20% or more and less than 30%. 3: The area ratio of the transferred material to the substrate is 100%, and the weight ratio of the transferred material is less than 20%. 2: The area ratio of the transferred area to the substrate is 50% or more and less than 100%. 1: The area ratio of the transferred area to the substrate is less than 50%. The industrially applicable levels above are rated 3, 4 and 5.

[0070] (Heat seal strength) The heat-sealed laminates obtained in the above Examples and Comparative Examples were cut into pieces measuring 15 mm x 100 mm, and the surfaces of the heat-sealed layers on the back side of the substrate were heat-sealed together using the following device and conditions, and the heat-seal strength and peeling state were evaluated. <Heat sealing conditions> Equipment: Heat seal tester manufactured by Tester Sangyo Co., Ltd., seal width: 10 mm, heater temperature: 130°C, seal pressure: 0.45 MPa, seal time: 1 sec <Heat seal strength measurement> Equipment: Intesco small tensile testing machine (model: IM-20), test piece width: 15 mm, peeling mode: 90° peeling, tensile speed: 300 mm / min 5: Peel resistance is 4N / 15mm or more and paper peels off over 100% of the heat-sealed area. 4: Peel resistance is 4N / 15mm or more, and the paper peels off over 50% or more but less than 100% of the heat seal area. 3: The peel resistance is 3N / 15mm or more and less than 4N / 15mm, and the base paper peels off in a manner that causes it to become frayed over 50% to 100% of the heat-sealed area. 2: Peel resistance is 0.5N or more but less than 3N / 15mm, and the paper does not peel off. 1: Peel resistance is less than 0.5N and is not heat sealed. The industrially applicable levels above are rated 3, 4 and 5.

[0071] (Blocking resistance) On the glossy surface (the surface not having the heat seal layer) of the substrate of the heat seal laminate obtained in the above Examples and Comparative Examples, Aqua PK Bioconc 39 Indigo manufactured by Toyo Ink Co., Ltd. was printed as an ink layer using a 250-line anilox roll at the above printing speed, and then Aqua TOP Water Repellent Varnish manufactured by Toyo Ink Co., Ltd. was printed as an overcoat layer on top of the ink layer using a 180-line anilox roll. The printed matter was cut into a size of 40 mm x 40 mm, and the surface of the overcoat layer and the surface of the heat seal layer were pressed together. The temperature was 40°C, the humidity was 80% RH, and the load was 1 kg / m 2 After leaving the sample for 18 hours under this environment, the peel resistance when the pressed surface was peeled off and the state of the peeled surface were evaluated according to the following criteria. 5: No peel resistance at all. 4: There is resistance to peeling, but no peeling of the ink layer or overcoat layer is observed. 3: Peel resistance is stronger than 4, but no peeling of the ink layer or overcoat layer is observed. 2: Strong peeling resistance, with peeling of the ink layer or overcoat layer being greater than 0% but less than 20% of the printed area. 1: The peeling resistance is very strong, and peeling of the ink layer or overcoat layer accounts for 20% or more of the printed area. The industrially applicable levels above are rated 3, 4 and 5.

[0072]

Table 1

[0073]

Table 2

[0074]

Table 3

[0075]

Table 4

[0076]

Table 5

Claims

1. The water-based heat sealing agent for flexographic printing contains an olefin-(meth)acrylic copolymer resin, and at least one member selected from a polyether resin, a poly(meth)acrylic acid resin, and a metal salt of a poly(meth)acrylic acid resin.

2. The water-based heat sealing agent for flexographic printing according to claim 1, wherein the olefin-(meth)acrylic copolymer resin contains an ethylene-(meth)acrylic acid copolymer resin.

3. 3. The water-based heat sealing agent for flexographic printing according to claim 1, wherein the olefin-(meth)acrylic copolymer resin has a flow midpoint temperature of 100 to 150°C.

4. The water-based heat sealing agent for flexographic printing according to any one of claims 1 to 3, wherein the polyether-based resin is a urethane-modified polyether resin.

5. A heat seal laminate comprising a paper substrate and a heat seal layer comprising the aqueous heat seal agent for flexographic printing according to any one of claims 1 to 4.

6. The heat sealable laminate according to claim 5, further comprising an anchor coat layer containing a styrene-(meth)acrylic copolymer resin.

7. A packaging material comprising the heat sealable laminate according to claim 5 or 6.

8. A method for producing a heat-sealable laminate having an anchor coat layer and a heat-sealable layer in this order on a paper substrate, comprising: The method for producing a heat-sealed laminate includes a step of forming an anchor coat layer on the paper substrate by flexographic printing an anchor coat agent containing a styrene-(meth)acrylic copolymer resin, and then a step of forming a heat-seal layer by flexographic printing an aqueous heat-seal agent containing an olefin-(meth)acrylic copolymer resin.

9. A method for producing a heat-sealable laminate having an anchor coat layer and a heat-sealable layer in this order on a paper substrate, comprising: A method for producing a heat-sealable laminate, comprising: a step of forming an anchor coat layer on the paper base material by flexographic printing an anchor coating agent; and a step of subsequently forming a heat-sealable layer by flexographic printing an aqueous heat-sealing agent for flexographic printing according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Laminated film and its manufacturing method

    JP2005238722A

  • Composition for heat sealing agent of water dispersion type

    JP2006282968A

  • Laminate

    JP2015189070A

  • Non-adhesive packaging bag for food product and production method thereof

    JP2016043990A

  • High Performance Waterborne Adhesive Compositions and Applications

    JP2017514935A